2012
DOI: 10.1002/path.3961
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of Stat3 in mammary epithelium impairs the acute phase response and modulates immune cell numbers during post‐lactational regression

Abstract: Mammary gland regression following weaning (involution) is associated with extensive cell death and the acquisition of an inflammatory signature. Characterizing the interplay between mammary epithelial cells, the re-emerging stroma and immune cells has implications for the understanding of the pathogenesis of pregnancy-associated breast cancer. Stat3 has a role in orchestrating cell death and involution, and we sought to determine whether expression of Stat3 by the mammary epithelium also influences the innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 49 publications
(86 reference statements)
7
94
0
Order By: Relevance
“…We further demonstrated that the deletion of JAK1 uncouples IL-6-class ligands from their downstream effector, STAT3. Consequently, this leads to the decreased expression of known STAT3 target genes that are associated with the acute-phase response, inflammation, and wound healing (42). The genome-wide expression analysis of JAK1-knockout mammary glands and control tissues revealed a number of novel target genes that were upregulated during involution in a JAK1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that the deletion of JAK1 uncouples IL-6-class ligands from their downstream effector, STAT3. Consequently, this leads to the decreased expression of known STAT3 target genes that are associated with the acute-phase response, inflammation, and wound healing (42). The genome-wide expression analysis of JAK1-knockout mammary glands and control tissues revealed a number of novel target genes that were upregulated during involution in a JAK1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be due to the inhibited activation of STAT3 in Nucling-KO mice. A previous study demonstrated that STAT3 activity directly or indirectly modulated M2 macrophage populations in postlactational mammary gland involution (27).…”
Section: Discussionmentioning
confidence: 96%
“…The Loss of Nucling Blocked STAT3 Activation by Repressing gp130 Expression-A recent study reported that STAT3 activity induced a M2 macrophage population during involution (27). Furthermore, the activation of STAT3 after weaning was required for normal mammary gland involution (7,8).…”
Section: Overexpression Of Nucling During Mammary Gland Involution-bementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of mast cell-derived PKaI during postlactational involution impaired epithelial cell death, suggesting that mast cells are vital for triggering apoptosis in the post-lactational mammary gland. Interestingly, in the absence of STAT3 within the mammary epithelium, mast cells and macrophages are not recruited to the mammary gland during post-lactational involution [108], suggesting that recruitment of stromal cells to the involuting mammary gland is initiated by early apoptotic signaling events occurring within the epithelial compartment (Fig. 1). …”
Section: Stromal-epithelial Interactionsmentioning
confidence: 99%